AN ANALYSIS OF VULNERABILITY OF SRAGEN REGENCY AGAINST THE CORONAVIRUS DISEASE 2019 PANDEMIC - Alfina Wijayanti; Sekar Kinasih Ningrum Prambudi; Farid Maulana Cempaka; Mursalin Ahmad; Muhammad Alfa Aqimmudin; Yunus Aris Wibowo (JURNAL GEOGRAFI, 2021)
In early 2020, WHO stated that Coronavirus Disease 2019 (Covid-19) is a new type of coronavirus with high transmission and fatality. Indonesia is one of the countries exposed to Covid-19, where there has been a fluctuation in the number of victims exposed to Covid-19 since March 2020. Sragen Regency is one of the areas affected by Covid-19. This study aims to determine the level of vulnerability of the Sragen Regency to the Covid-19 pandemic and analyze the relationship between regional vulnerability and the number of Covid-19 cases (suspect, probable, confirmed, and discarded cases) in Sragen Regency. This research was conducted quantitatively by descriptive and inferential statistical analysis using the Spearman Rho test, preceded by tests of normality and homogeneity as a prerequisite test. The results indicated that the vulnerability of the Sragen Regency to Covid-19 was classified into high, medium, and low classes. High class dominated in 11 districts, medium class in 8 districts, and low class in 1 sub-district. Furthermore, the Spearman's rho test results were 0.084>0.05, which means that there was a relationship between the regional vulnerability variable and the number of Covid-19 cases, but it was not significant. That is because of the effective handling of the Covid-19 pandemic and the high level of community awareness in the Sragen Regency.Keywords: Covid-19, Disaster, Pandemic, Regional Vulnerability, Sragen